PERANCANGAN INFRASTRUKTUR JARINGAN KOMPUTER UNTUK MENDUKUNG IMPLEMENTASI SISTEM INFORMASI PADA UNIVERSITAS TEKNOLOGI SUMBAWA - Shinta Esabella (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
The purpose of this writing is to be able to recognize the performance of the design of computer networks of Universitas Teknologi Sumbawa which has been built in simulator OPNET Version 14.5, from which the design of a computer network consists of two designs specifically design of computer networks using Cable Media and Wireless Media (Access Point). The study begins by analyzing the current situation of the computer network and discovers the circumstance of utilization of computer networks had not been optimal as the condition of the computer network infrastructure of Universitas Teknologi Sumbawa rector is only found in the main building itself. The process of analysis and design of computer network infrastructure uses the Network Development Life Cycle (NDLC). The comparison outcome of the design with the Cable Media in the Simulator has Page Response Time 82,3% faster than using Wireless Media and delay point of Cable Media is 19,1% lower than Wireless Media. Therefore Cable Media is able to be considered as one of preferences by the Executive Board of Universitas Teknologi Sumbawa to develop Computer Network Infrastructure for integrating entire existing building within the campus area in order to support the implementation of the information system.